Brian's return - Paulsen, Gary. (2001)
After having survived alone in the wilderness, Brian finds that he can no longer live in the city but must return to the place where he really belongs.
Keywords: Self-reliance -- Juvenile fiction; Wilderness areas -- Juvenile fiction; Survival -- Juvenile fiction; Fiction